2010
DOI: 10.1016/j.ejvs.2010.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Mechanical Changes in Juxtarenal Aortic Segment and Aneurysm Before and After Open Surgical Repair of Abdominal Aortic Aneurysms

Abstract: Disorganisation and destruction of normal aortic architecture at the ultrastructural level are associated with decreasing aortic distensibility. Low aortic neck distensibility is associated with proximal aortic dilatation at 2 years postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In fact, aortic disease progresses independent of the type of repair (open or endovascular), endograft, or neck length. In a prospective study of 30 patients with short aortic necks treated using open repair, Majewski and colleagues 4 observed that 60% of the patients demonstrated enlargement at or above the anastomosis, averaging 5 mm after 2 years. In that study, biopsy of the anastomotic aortic wall at initial operation revealed degeneration of the normal cellular architecture, indicating that even “normal” appearing aortic segments are already diseased.…”
mentioning
confidence: 99%
“…In fact, aortic disease progresses independent of the type of repair (open or endovascular), endograft, or neck length. In a prospective study of 30 patients with short aortic necks treated using open repair, Majewski and colleagues 4 observed that 60% of the patients demonstrated enlargement at or above the anastomosis, averaging 5 mm after 2 years. In that study, biopsy of the anastomotic aortic wall at initial operation revealed degeneration of the normal cellular architecture, indicating that even “normal” appearing aortic segments are already diseased.…”
mentioning
confidence: 99%
“…Disorganization and destruction of normal aortic architecture at the ultrastructural level are associated with decreasing aortic distensibility, with low aortic neck distensibility being associated with proximal aortic dilatation at 2 years postoperatively (53). According to many authors, disease progression may be the most common underlying culprit for proximal false-aneurysm formation (54).…”
Section: Progression Of Proximal Aaa Neck After Open Surgerymentioning
confidence: 99%
“…Second, the majority of studies assessing neck morphology after treatment (23, 30, 52, 53, 58) have not used a life-table or Kaplan–Meier analysis as a main method of statistical analysis. Thus, another core requirement of the SVS reporting standards was not fully met.…”
Section: Heterogeneity Of Datamentioning
confidence: 99%
“…Aortic neck dilatation is likely to be caused by morphological and histological changes. 2,3 The most important deficiency of the majority of commercially available endografts today is the inability to adequately withstand longitudinal migration forces or to resist aortic dilatation.…”
mentioning
confidence: 99%